2011
DOI: 10.1088/0004-637x/736/1/28
|View full text |Cite
|
Sign up to set email alerts
|

A Population of X-Ray Weak Quasars: PHL 1811 Analogs at High Redshift

Abstract: We report the results from Chandra and XMM-Newton observations of a sample of 10 type 1 quasars selected to have unusual UV emission-line properties (weak and blueshifted high-ionization lines; strong UV Fe emission) similar to those of PHL 1811, a confirmed intrinsically X-ray weak quasar. These quasars were identified by the Sloan Digital Sky Survey at high redshift (z ≈ 2.2); eight are radio quiet while two are radio intermediate. All of the radio-quiet PHL 1811 analogs, without exception, are notably X-ray… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
192
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(212 citation statements)
references
References 113 publications
12
192
0
Order By: Relevance
“…In this scenario, such PHL 1811 analogs are a subset of WLQs, viewed through the shielding gas while "normal" WLQs are viewed at lines of sight that do not intersect this component. This may explain the observed X-ray weakness and apparently hard X-ray spectra of the PHL 1811 analogs (Wu et al 2011), although it is more difficult to explain the very steep (soft) X-ray spectrum of PHL 1811 itself using this model (Leighly et al 2007b).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this scenario, such PHL 1811 analogs are a subset of WLQs, viewed through the shielding gas while "normal" WLQs are viewed at lines of sight that do not intersect this component. This may explain the observed X-ray weakness and apparently hard X-ray spectra of the PHL 1811 analogs (Wu et al 2011), although it is more difficult to explain the very steep (soft) X-ray spectrum of PHL 1811 itself using this model (Leighly et al 2007b).…”
Section: Discussionmentioning
confidence: 95%
“…Wu et al (2011) suggest that the weakness of the UV lines in their PHL 1811 analogs is due to a larger than usual high-ionization "shielding gas" component that covers most of the BELR, but little more than the BELR in such sources. In this scenario, such PHL 1811 analogs are a subset of WLQs, viewed through the shielding gas while "normal" WLQs are viewed at lines of sight that do not intersect this component.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An unexpected population of ∼10 2 quasars were discovered within the spectra of the Sloan Digital Sky Survey (SDSS; York et al 2000) that display exceptionally weak or completely missing broad emission lines in the ultraviolet (UV) rest-frame (Fan et al 1999;Anderson et al 2001;Collinge et al 2005;Diamond-Stanic et al 2009, hereafter DS09;Plotkin et al 2010a, hereafter P10;Hryniewicz et al 2010;Wu et al 2011;Meusinger & Balafkan 2014). The first systematic search for such weak emission line quasars (WLQs) was performed by DS09, who examined the rest-frame equivalent width (W r ) distribution of the Lyα λ1216+N V λ1240 blend for SDSS quasars at z > 3.…”
Section: Introductionmentioning
confidence: 99%
“…Various suggestions have been made to explain the absence of broad lines in unobscured quasars (e.g., Shemmer et al 2010;Laor & Davis 2011, and references therein) but this AGN type remains puzzling. A subset of quasars with weak UV emission lines have been identified that are known as PHL 1811 analogs (Leighly et al 2001;Leighly et al 2007;Wu et al 2011Wu et al , 2012. Leighly et al (2007) suggested that the weak UV emission lines of these objects are due to an unusual soft SED deficient in ionising photons, perhaps due to exceptionally high Eddington ratios (see e.g., Shemmer et al 2009, and references therein).…”
Section: Introductionmentioning
confidence: 99%